WAVES SPEED AVERAGING IMPACT ON GODUNOV TYPE SCHEMES FOR HYPERBOLIC EQUATIONS WITH DISCONTINUOUS COEFFICIENTS: THE LINEAR SCALAR CASE - Remaki, L. (European Journal of Applied Sciences, 2022)
This paper deals with the waves speed averaging impact impact on Godunov type schemes for linear scalar hyperbolic equations with discontinuous coefficients. In many numerical schemes of Godunov type used in fluid dynamics, electromagnetic, electro- hydrodynamic problems and so on, usually a Riemann problem needs to be solved to estimate fluxes. The exact solution is generally not possible to obtain, but good ap- proximations are provided in many situations like Roe and HLLC Riemann solvers in fluids. However all these solvers assume that the acoustic waves speed are continuous by considering some averaging. This could unfortunately lead to a wrong solution as we will show in this paper for the linear scalar case. Providing a Riemann solver in the general case of non-linear hyperbolic systems with discontinuous waves speed is a very hard task, therefore in this paper and as a first step, we focus on the linear and scalar case. In a previous work we proposed for such problems a Riemann solution that takes into account the discontinuities of the waves speed, we provided a numeri- cal argument to show the validity of the solution. In this paper, first a new argument using regularization technique is provided to reinforce the validity of the proposed solution. Then, the corresponding Godunov scheme is derived and the effect of waves speed averaging is clearly demonstrated with a clear connection to the distribution product phenomenon.